PERILAKU PERAWAT DALAM PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI IRNA MEDIKAL RSUD PEKANBARU 2016 - Putri Wulan Dini (LPPM Universitas Abdurrab, 2017)
The humanistic professional service nursing, is done based on the science and nursing trick, with the orientation on the client’s objective need. Behavior is the entire human’s activity, it can be directly or indirectly observed by the outsiders. The self-protection equipment using is the equipment which is used by the health workersto0 protect all bodies through existence of the working accident/ dangerous for reaching the working safety. Purpose of the research was to determine the behavior (knowledge, attitude and action) of the nurse about the self-protection equipment using in overcoming the HIV/ AIDS at the medical inpatient of third class of Arifin Achmad hospital in 2016. Purpose of the research was to reduce the working accident amount. The operated maintain in the research was quantitative by analytic descriptive method to explain description of the nurse’s behavior about the self-protection equipment using. To know about